APPLICATION OF GENERALIZED DERIVATIVE OPERATOR ON BOUGUER ANOMALY FOR DETECTING GEOLOGICAL STRUCTURES - Dicky Ahmad Zaky; Alissa Bilqis (JGE (Jurnal Geofisika Eksplorasi), 2022)
Generalized Derivative Operator (GDO) is one of the first-order derivative filters that could control the derivative’s direction by modifying the value of azimuth () and dip () parameters. This study aims to examine those GDO parameters on synthetic Bouguer anomaly and apply them to field data of the Silver Peak geothermal field to identify the geological structures. We use Python programs to conduct the GDO and other derivative operators such as horizontal gradient (HG), analytic signal amplitude (AS), as well Second Vertical Derivative (SVD) for comparison. The derivative operators are performed in the Fourier domain and spatial domain. The results from synthetic data show that GDO can amplify the response both on local and regional anomalies. Nevertheless, enhanced local and regional anomaly might be shown as the same maximum value of GDO. It appears that GDO disregard the influence of density contrast and depth variation of the anomalous body. Subsequently, anomaly enhancement of Silver Peak area shows that GDO anomaly concurred with geological map. GDO and SVD could amplify the response of geological structures such as intrusive granite, fault lineaments, and lithological contact, as well as the horst-graben structure, as mentioned in previous studies, that might be acting as fluid pathways for the Silver Peak geothermal system.